Tanfidh Istiratijiaat Mubtakarat Litadris Al-Istima’i Waltahaduts Fi Ta’lim Allughatul ‘Arabiyah Fi Al-Madaris Al-Ibtidaiyah - Baharudin, Amaliyah Ananda; Taufik, Taufik; Hidayah, Taufikan; Khairani, Ismi; Rahmawati, Laili (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
Learning Arabic as a foreign language certainly requires a strategy that can make students interested in learning it. In addition, there are strategies to help teachers overcome boredom in learning so that it is hoped that the learning that will be created will be much more interactive and fun. So, the purpose of this article is to analyze innovative learning strategies for learning istima' and kalam in learning Arabic at Islamic elementary schools. The results obtained from our research include several activities that support innovative istima and kalam strategies, namely: (1) active learning, (2) technology-based learning, (3) structured speaking exercises, (4) using relevant material, (5) using language games, (6) support discussion, (7) use of Multimedia, (8) Collaborative learning. This activity is considered effective for increasing students' understanding both in terms of knowledge and skills